Use of Information Technology in Relation to Technology Beliefs and Attitudes - Bai A. Hua (International Journal of Instructional Technology, 2022)
This study explored teacher educators’ pedagogical beliefs and technology uses in relation to preservice teachers’ pedagogical beliefs and attitudes toward technology. Correlation and regression analysis were conducted to answer the research questions. The results revealed some relationships between the teacher educators’ beliefs and their uses of technology. In addition, it was found that the teacher educators’ learner centered beliefs could influence the preservice teachers’ learner-centered beliefs. The frequency that the teacher educators had the preservice teachers use technology in both constructivist and traditional way could influence the preservice teachers’ attitudes toward technology.